Результати інтродукційних та фітохімічних досліджень видів роду Dracocephalum L. (D. grandiflorum L. та D. moldavica L.) у Північному Лісостепу та на Західному Поділлі України - Shanayda, M.I.; Pasemkiv, Yu.A.; Korablova, O.A.; Rakhmetov, D.B. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
The results of introduction and phytochemical researches of species genera Dracocephalum L. (D. grandiflorum and D. moldavica) under condition of Western Podillja and North Forest-Steppe of Ukraine are presented. Peculiarities growth and development of the plants, quality of above-ground part and seeds of species D. grandiflorum and D. moldavicа, contents phenolics, vitamin C, components composition of essential oil of the plants, micro- and macroelements composition of grass were analyzed with aim use of them for pharmaceutical and food industries.